INTEGRATED SUPPLY CHAIN STRATEGY WITH STANDARDIZATION OF PROFESSIONAL COMMUNICATION AS LEAN MANUFACTURING TOOL - A. Kucheryavenko, Svetlana; A. Gayvoronskaya, Svetlana; V. Chistnikova, Irina; E. Vinnik, Alina (International Journal of Supply Chain Management, 2019)
Abstract-The article substantiates the importance of professional communication standardization and supply chain strategy as lean manufacturing tool, which is loss reduction reserve in the organizations of different fields. They consider the issues of organization effectiveness impact in the field of communication processes, and the effectiveness of its work in general. They provided the definition of professional communication standardization process, the main conditions for its occurrence are highlighted. The formation of lean communication is proposed as the result of professional communication standardization. They summarized the advantages of standardized professional communication gained by the company.